Middle Paleozoic convergent orogenic belts in western Inner Mongolia (China): framework, kinematics, geochronology and implications for tectonic evolution of the Central Asian Orogenic Belt - Xu, Bei; Charvet, Jacques; Chen, Yan; Zhao, Pan; Shi, Guanzhong (Gondwana research, 2013)
Based mainly on field geological observation and geochronologic data, six tectonic units have been recognized in western Inner Mongolia (China), including, from south to north: North China Craton (NCC), Southern Orogenic Belt (SOB), Hunshandake Block (HB), Northern Orogenic Belt (NOB), South Mongolia microcontinent (SMM), and Southern margin of Ergun Block (SME), suggesting that the tectonic framework of the CAOB in western Inner Mongolia is characterized by an accretion of different blocks and orogenic belts. The SOB includes, from north to south, fold belt, mélange, arc-pluton belt, and retroarc foreland basin, representing a southern subduction–collision system between the NCC and HB blocks during 500–440Ma. The NOB consists also of four units: arc-pluton belt, mélange, foreland molasse basin, and fold belt, from north to south, representing a northern subduction–collision system between the HB and SMM blocks during 500–380Ma. From the early Paleozoic, the Paleo-Asian oceanic domains subducted to the north and the south, resulting in the forming of the SOB and the NOB in 410Ma and 380Ma, respectively. This convergent orogenic system, therefore, constrained the consumption process of the Paleo-Asian Ocean in western Inner Mongolia. A double subduction–collision accretionary process is the dominant geodynamic feature for the eastern part of the CAOB during the early to middle Paleozoic. [Display omitted] ► We describe a Southern and a Northern orogenic belts in western Inner Mongolia. ► They constitute a middle Paleozoic convergent orogenic system. ► A double subduction–collision process led to closure of eastern Paleo-Asian Ocean.